Next-generation (epi)genetic drivers of childhood brain tumours and the outlook for targeted therapies - Northcott, Paul A.; Pfister, Stefan; Jones, David T. W. (The lancet. Oncology, 2015)
Summary: Arguably, nowhere has there been a greater advance in our understanding of biological mechanisms and potential translational targets during the next-generation sequencing era than in paediatric brain tumours. The so-called omics revolution, enabled by high-throughput sequencing, has empowered large consortia and independent groups alike to make major genetic discoveries, from dominant-negative histone mutations and hijacking of distal enhancer elements, to new oncogenic gene fusions and aberrantly active gene expression. Epigenetic deregulation has also been revealed as a common theme across several tumour subtypes. This Review focuses on key findings that have been transforming the landscape of paediatric neuro-oncology research and how these results are opening new avenues towards potential therapeutic translation.
Gesehen am 11.04.2017